Micro-modeling of thermal properties in carbon fibers reinforced polymer composites with fiber breaks or delamination. (1st April 2017) - Ning, Zhihua; Liu, Renhuai; Elhajjar, Rani F.; Wang, Fan
Abstract: The thermal properties can be correlated to fiber breaks and delamination in unidirectional carbon fibers reinforced polymer (CFRP) composites by an analytical model developed in the present study. According to classical thermal laws, the thermal characteristics of the composite will change when the defects induce gaps or discontinuities in the composite. The thermal resistance with fiber breaks was obtained by cutting the contribution of a broken fiber on total resistance with the assumption of heat flow into the CFRP sample along the fiber longitudinal direction. Similarly, a delamination was treated as an air-filled defect which produces extra resistance to the original composite with the assumption of heat flow into the sample in the thickness direction. Analytical solutions were derived to predict the thermal resistance as a function of number of fiber breakage or delamination lateral size. The results show that the thermal resistance increases linearly with increasing the number of fiber breaks or delamination area. Thus thermal resistance can be a precise indicator of fiber breaks and delamination in CFRP composites. Fiber breaks degrade considerably the heat transfer ability of CFRP on longitudinal direction, while much less on the thickness direction. The effects of fiber volume fraction and ratio of fiber/matrix conductivity on thermal properties of the composite were discussed. The analytical solutions are in good agreement with the results from finite element analysis. The solution was also applied on the method of pulse thermography, and it was found that, the defect region, whether fiber breakage or delamination, will lead to changes in the temperature distribution on the rear surface of the composite. The thermal contrast is sensitivity to carbon fiber volume fraction. The present study proposed a simple way to correlate the thermal response to mechanical damages at the micro-scale in CFRP composites.